UV-Protection Effect of Nanoemulgel Formulation from Moringa oleifera Lam. Leaf Extracts in Rattus novergicus - Arie Tika Anditha; Linda Chiuman; Chrismis Novalinda Ginting (Jurnal Penelitian Pendidikan IPA, 2024)
Exposure to sunlight (UV radiation) can harm the skin, leading to cancer and tissue damage. The body’s natural defense involves activating hormones that stimulate melanin synthesis to reduce cellular damage. Moringa oleifera Lam. leaves, rich in flavonoids and phenolic compounds, are promising UV-protection agents. This study assessed the efficacy of nanoemulgel formulations containing M. oleifera leaf extract through in vitro and in vivo assays. Twenty-five rats were divided into five groups, including formulations with 2%, 3%, and 4% M. oleifera extract, a negative control, and a positive control with Azarine Sunscreen Gel SPF 45. The nanoemulsions had appropriate size and quality, with the highest SPF observed at 4% concentration (7.95±0.06). According to FDA classification, these formulations fall within the 'extra' SPF category (6<SPF<8). However, melanin scores in the nanoemulgel groups were comparable to the untreated control, and the 4% concentration (44.4±16.3) did not match the protection provided by commercial sunscreen (10.0±1.58). These findings suggest M. oleifera has potential for photoprotection, but further optimization is needed.